Inferring Annotations For Device Drivers From Verification Histories - Pavlinovic, Zvonimir; Lal, Akash; Sharma, Rahul (Automated Software Engineering (ASE), 2016)
This paper studies and optimizes automated program verification. Detailed reasoning about software behavior is often facilitated by program invariants that hold across all program executions. Finding program invariants is in fact an essential step in automated program verification. Automatic discovery of precise invariants, however, can be very difficult in practice. The problem can be simplified if one has access to a candidate set of assertions (or annotations) and the search for invariants is limited over the space defined by these annotations. Then, the main challenge is to automatically generate quality program annotations. We present an approach that infers program annotations automatically by leveraging the history of verifying related programs. Our algorithm extracts high-quality annotations from previous verification attempts, and then applies them for verifying new programs. We present a case study where we applied our algorithm to Microsoft's Static Driver Verifier (SDV). SDV is an industrial-strength tool for verification of Windows device drivers that uses manually-tuned heuristics for obtaining a set of annotations. Our technique inferred program annotations comparable in performance to the existing annotations used in SDV that were devised manually by experts over years. Additionally, the inferred annotations together with the existing ones improved the performance of SDV overall, proving correct 47% of drivers more while running 22% faster in our experiments.
ACM SIGSOFT Distinguished Paper Award